Participation of the GABAergic system on the glutamate release of frontal cortex synaptosomes from Wistar rats with experimental autoimmune encephalomyelitis - Cid, Mariana Paula (2011)
We previously found that the glutamate release was decreased in synaptosomes from rat cerebral cortex during the development of experimental autoimmune encephalomyelitis (EAE), the animal model of multiple sclerosis. Various other reports have shown a deficit in the expression of proteins associated with GABAergic neurotransmission in the neocortex of patients with multiple sclerosis and it was also demonstrated that the activation of GABA A receptors leads to an inhibition of glutamate release. Now, in order to evaluate the events that may affect the neuronal function in EAE synaptosomes, we analyzed the participation of the GABAergic system in glutamate release and in the flunitrazepam-sensitive GABA A receptor density. This revealed alterations in the GABAergic system of the frontal cortex synaptosomes from EAE animals. GABA induced a decrease in the 4-aminopyridine-evoked glutamate release in control synaptosomes which was abolished by picrotoxin, a GABA A receptor antagonist. In contrast, synaptosomes from EAE rats showed a loss in the inhibition of glutamate release mediated by GABA. Furthermore, the flunitrazepam-sensitive GABA A receptor density was decreased during the acute stage of the disease in synaptosomes from EAE rats. We also observed a loss of inhibition in the Ca 2+-dependent phosphorylation of synapsin I mediated by GABA in nerve terminals from EAE animals, which could explain the loss of GABAergic regulation on evoked glutamate release. The changes observed in the GABA A receptor density as well as the loss of GABAergic inhibition of glutamate release were partially reverted in cortical synaptosomes from recovered EAE animals. These results suggest that the decrease in the flunitrazepam-sensitive GABA A receptor density may explain the observed failure of GABAergic regulation in the glutamate release of synaptosomes from EAE rats, which might contribute to the appearance of clinical symptoms and disease progression.